2010
DOI: 10.1093/jxb/erp400
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of SCARECROW genes expressed in white lupin cluster roots

Abstract: The Scarecrow (SCR) transcription factor plays a crucial role in root cell radial patterning and is required for maintenance of the quiescent centre and differentiation of the endodermis. In response to phosphorus (P) deficiency, white lupin (Lupinus albus L.) root surface area increases some 50-fold to 70-fold due to the development of cluster (proteoid) roots. Previously it was reported that SCR-like expressed sequence tags (ESTs) were expressed during early cluster root development. Here the cloning of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
(92 reference statements)
1
28
0
Order By: Relevance
“…Evidence suggested that PDR2 is imperative for maintaining SCR protein during P starvation. White lupin SCRs (LaSCR1 and LaSCR2) have been isolated and recently characterized (Sbabou et al, 2010). Consistent with the localization of SCR genes in all the species examined to date (Pysh et al, 1999;Sassa et al, 2001;Kamiya et al, 2003;Laajanen et al, 2007), the expression of LaSCR genes has been localized to the root endodermis and quiescent center and seems to be closely related to cluster root development rather than to the P status of the plant.…”
Section: P Signaling: Systemic Versus Localmentioning
confidence: 55%
See 1 more Smart Citation
“…Evidence suggested that PDR2 is imperative for maintaining SCR protein during P starvation. White lupin SCRs (LaSCR1 and LaSCR2) have been isolated and recently characterized (Sbabou et al, 2010). Consistent with the localization of SCR genes in all the species examined to date (Pysh et al, 1999;Sassa et al, 2001;Kamiya et al, 2003;Laajanen et al, 2007), the expression of LaSCR genes has been localized to the root endodermis and quiescent center and seems to be closely related to cluster root development rather than to the P status of the plant.…”
Section: P Signaling: Systemic Versus Localmentioning
confidence: 55%
“…Consistent with the localization of SCR genes in all the species examined to date (Pysh et al, 1999;Sassa et al, 2001;Kamiya et al, 2003;Laajanen et al, 2007), the expression of LaSCR genes has been localized to the root endodermis and quiescent center and seems to be closely related to cluster root development rather than to the P status of the plant. Suppression of LaSCR1 transcripts in transgenic lupin roots resulted in reduced cluster root numbers, implying a role for LaSCR1 in maintaining root growth in white lupin (Sbabou et al, 2010).…”
Section: P Signaling: Systemic Versus Localmentioning
confidence: 98%
“…Southern blot analysis using a molecular probe specific to a region encoding a conserved domain confirmed that there are no closely related paralogues of the CsSCR gene in the cucumber genome. This is in contrast to white lupin, in which two highly similar SCS genes, that play a role during cluster root development, were identified (Sbabou et al 2010).…”
Section: Discussionmentioning
confidence: 65%
“…SCR is involved in root radial patterning in A. thaliana (Di Laurenzio et al 1996;Benfey et al 1993;Scheres et al 1995), and the expression patterns of AtSCR orthologues can suggest a similar function in maize (Lim et al 2000(Lim et al , 2005, pea (Sassa et al 2001), rice (Kamiya et al 2003), Pinus sylvestris (Laajanen et al 2007) and white lupin (Sbabou et al 2010). In A. thaliana, SCR and another GRAS family member SHR (SHORT ROOT) play a key role in specification of the cortex and endodermis cell layers, which are located between the epidermis and the pericycle.…”
Section: Introductionmentioning
confidence: 99%
“…White lupin plants are recalcitrant to stable transformation: Agrobacterium tumefaciens-mediated transformation has not been successful so far. Transformed-hairy roots induced by the infection of A. rhizogenes have been used to elucidate the functions of endogenous genes (Cheng et al 2011a;Sbabou et al 2010;Uhde-Stone et al 2005), although shoots cannot be regenerated from hairy roots. Thus, genetic transformation is of limited use for the study of white lupin genes, especially those expressed in shoots.…”
mentioning
confidence: 99%